Implementation of Contextual Based Teaching Materials on Various Work Themes of Primary School Students - Rismaningtyas, Arista; Slamet, Achmad; Pranoto, Yuli Kurniawati Sugiyo (Journal of Primary Education)
This study aimed to analyze the hypothetical model and analyze the effectiveness of the use of teaching materials. The research design used in this study is research and development. The study was conducted in elementary schools in the District Diponegoro Force Gringsing Batang with research subjects fourth-grade learners at three elementary schools SDN Yosorejo, SDN Krengseng 2, and SDN Sidorejo 1. Sources of research data derived from the expert of experts, education professionals, and learners, The data collection method used measurement scales and tests. Teaching materials developed using seven syntax contextual learning model that integrates seamlessly with the theme of learning various jobs. The results of product validation by expert gets an average value of 3.34 with a percentage of 83.58%. It shows that the product of teaching materials in this study deserves to be tested further. The results showed that an increase in outcomes after using the instructional materials with N-Gain test results on a limited scale trial of 0.55 with category and 0.50 on the results of the use of teaching materials are also categorized as moderate.